Officiating, coaching and health education in physical education - Rokade, P.R. Dr. (Jaipur, India ABD Publishers, 2018)
The major purposes of the health, physical education and recreation program are; to provide for the preparation and improvement of skilled health teachers, of physical education teachers, of recreation leaders, and of coaches; to provide a meaningful instructional program, curricular and extra-curricular, in health, physical education and recreation for all students; to provide professional leadership for the athletic and recreational activities and plans of the students. Sports officials, also known as umpires or referees, apply and enforce the rules and regulations in a professional manner during sporting event. Their primary goal is to provide quality supervision to maintain a safe environment for the sport participants, spectators and fellow officials. This resource guide will help teachers and administrators see their roles and responsibilities in a new light and gain stakeholder support for wellness and activity programs, and it will assist in coordinating efforts among all involved in providing students with safe and appropriate programs that will transform their schools into more active places for learning
Officiating of games and sports -- Coaching of games and sports -- Origin and development of games and sports -- Training methods in games and sports -- Types of training method in games and sports -- Health education -- Contemporary health problems -- Family and health problems -- Family and health education -- Recreation in physical education and sports
First published in India, 2018
Includes bibliographical references and index